Interferon-α as maintenance therapy can significantly reduce relapse in patients with favorable-risk acute myeloid leukemia. Issue 12 (15th October 2021) - Jiang, Hao; Liu, Xiao-Hong; Kong, Jun; Wang, Jing; Jia, Jin-Song; Lu, Sheng-Ye; Gong, Li-Zhong; Zhao, Xiao-Su; Jiang, Qian; Chang, Ying-Jun; Wang, Yu; Ruan, Guo-Rui; et al.
Abstract: To evaluate the efficacy of interferon-α (IFN-α) as maintenance therapy in patients with favorable-risk acute myeloid leukemia (AML), this retrospective study enrolled 84 patients with favorable-risk AML: 42 patients who received IFN-α maintenance therapy and 42 patients who did not (control). The median follow-up time and duration of IFN-α treatment was 26 (6–54) months and 18 (2–24) months, respectively. The 4-year estimated relapse-free survival (RFS) after the last consolidation chemotherapy was 86.8% (95% confidence interval (CI), 75.8–97.8%) in the IFN-α group and 55.7% (95% CI, 37.2–74.3%) in the control group ( p =.007). The 4-year estimated overall survival was 94.4% (95% CI, 86.8–102%) and 76.4% (95% CI, 61.9–90.9%) in IFN-α and control groups, respectively ( p =.040). The Cox regression analysis showed that IFN-α treatment was the only independent factor affecting RFS ( p =.004). Maintenance therapy with IFN-α may prevent relapse in favorable-risk AML after consolidation chemotherapy.